Creativitites : the what, how, where, who and why of the creative process - Bilton, Chris; Cummings, Stephen; ogilvie, dt (Edward Elgar Publishing, 2022)
"What is creativity and how can we best nurture creativity in different contexts? Drawing on a wide range of cases from the arts, business, design, media and sports, Creativities encourages readers to discover, mix and adapt their own version of creativity, rather than attempting to imitate or follow 'best practice'. International in scope, examples and cases extend beyond the typical Western 'creative genius' model, illuminating the great extent and diversity of global creativities. The book is designed around five key questions that address the what, how, where, who and why of the creative process, employing frameworks, questions and illustrative 'recipes' designed to inspire out-of-the-box creative thinking. The authors argue that to develop their own creativities, readers should experiment with different ingredients and find their own bisociative balance. With its rich array of cases, frameworks and visual material, Creativities will help educators design and lead classes on creativity, innovation and creative entrepreneurship. Its accessible content will also appeal to and inspire students and practitioners in business leadership, organisational innovation and critical management studies"--